Desain Pembelajaran Materi Produktivitas Menggunakan Pendekatan STEM Pada Mata Kuliah Ekologi - Budhi Utami; Poppy Rahmatika Primandiri; Tutut Indah Sulistiyowati; Mohammad Farid Zamzami (Universitas Nusantara PGRI Kediri, 2022)
Productivity is one of the materials studied in ecology courses. As a result of the interview, many students still have difficulty in understanding this material and lecturers also have difficulty designing learning that connects context with the environment. Therefore, student learning activities need to be designed with a STEM approach. The research aims to produce a learning trajectory to help students on productivity materials using STEM approaches. The method used in this research is a design research type validation study consisting of three stages: preparing for the experiment, experiment in the classroom (pilot experiment & Teaching experiment), and restrospective analysis. The research subjects were 6 students and 3 lecturers. Research instruments in the form of interview sheets for students and lecturers and using student metacognitive questionnaires. The results of this study show that through a series of activities that have been done, learning using STEM can help students understand productivity materials and become a starting point in the learning process